Preparation and Effect of Selenium Nanoparticles/Oligochitosan on the White Blood Cell Recovery of Mice Exposed to Gamma-Ray Radiation - Duy Ngoc Nguyen; Phu Van Dang; Quoc Anh Le; Lan Thi Kim Nguyen; Hien Quoc Nguyen; Ngan Thi Thu Tran; Ha Le Bao Tran; Tuan Dinh Phan; Ha Manh Bui (Journal of Chemistry)
Owing to their excellent bioavailability, high bioactivity, and low toxicity, selenium nanoparticles (SeNPs) are emerging nanomaterials. In this study, SeNPs with a size of ∼41.8 nm were synthesised by γ-irradiation using oligochitosan (OCS) as the stabiliser. As-synthesized SeNPs/OCS were characterised by UV-Vis spectroscopy, transmission electron microscopy, and energy-dispersive X-ray (EDX) analysis. Results revealed that the as-obtained SeNP/OCS powder exhibits high purity. The SeNP/OCS solution’s stability test results indicated that the SeNP/OCS solution stored at 4°C exhibits good stability for 60 days. The SeNP/OCS solution was unstable at ambient temperature, and SeNP/OCS exhibited agglomeration after about 15 days. SeNP/OCS products recovered the total white blood cells of γ-ray irradiated mice. The SeNP/OCS product, which was synthesised by a green approach, with high purity and efficient recuperation of white blood cells, can be used potentially as a functional supplement to assist cancer radiotherapy patients.